2019
DOI: 10.3390/md17110604
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Applications of Scyphomedusae

Abstract: As people across the world live longer, chronic illness and diminished well-being are becoming major global public health challenges. Marine biotechnology may help overcome some of these challenges by developing new products and know-how derived from marine organisms. While some products from marine organisms such as microalgae, sponges, and fish have already found biotechnological applications, jellyfish have received little attention as a potential source of bioactive compounds. Nevertheless, recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 152 publications
(96 reference statements)
3
72
0
2
Order By: Relevance
“…However, as reported by [ 11 , 16 ], receptor site three has been identified as the binding site for sea anemone Type I and Type III sodium channel inhibitors. Toxins have been recently reviewed in Scyphozoa [ 13 , 14 , 17 ] and in sea anemones (Actinaria) [ 11 , 14 ]. In this review, we provide an updated synopsis of the main compounds identified to present in the venom of cnidarians and discuss the recent application of omics and biotechnological tools in the field.…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
See 2 more Smart Citations
“…However, as reported by [ 11 , 16 ], receptor site three has been identified as the binding site for sea anemone Type I and Type III sodium channel inhibitors. Toxins have been recently reviewed in Scyphozoa [ 13 , 14 , 17 ] and in sea anemones (Actinaria) [ 11 , 14 ]. In this review, we provide an updated synopsis of the main compounds identified to present in the venom of cnidarians and discuss the recent application of omics and biotechnological tools in the field.…”
Section: Venoms Of Cnidariamentioning
confidence: 99%
“…The crude venom extracted from cnidarians has a wide range of effects on humans, such as dermonecrosis, edema, diffused neurotoxicity, motorial and respiratory problems, cardiovascular symptoms, hypotension and occasionally death [ 17 ]. Cytotoxic, cytolytic, hemolytic and neurotoxic activities are the most common effects observed for crude Cnidaria venom ( Table 2 ).…”
Section: Cnidaria Bioprospectingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review has shown that rhizostome scyphomedusae contain more collagen than semaeostomeae scyphomedusae [51], as shown in Table 1. The collagen content in Rhopilema esculentum is significantly high, considering that the value in Table 1 is based on dry mass.…”
Section: Introductionmentioning
confidence: 99%
“…Jellyfish extracted molecules (proteins, peptides, mucins) have antioxidant, wound healing and antimicrobial properties (Merquiol et al, 2019;Nudelman et al, 2019). The most famous jellyfish-derived compound is the green fluorescent protein (GFP), one of the most important tools in molecular biology research, serving as a molecular marker alongside other that found important applications in wider scientific research, and was awarded the Nobel Prize in Chemistry in 2008 to Osamu Shimomura, Martin Chalfie, and Roger Tsien.…”
Section: Potential Future Prospects In Healthcare and Well-beingmentioning
confidence: 99%